Exploring the Experiences and Well-Being of Australian Rio Olympians During the Post-Olympic Phase: A Qualitative Study - Bennie, Andrew; Walton, Courtney C.; O’Connor, Donna; Fitzsimons, Lauren; Hammond, Thomas (Frontiers in Psychology, 2021)
Research about the Olympic Games has primarily focused on preparing athletes for competition. Less attention has been paid to the post-Olympic-phase (POP) and athlete well-being during this time. This study explored Australian Olympic athletes’ experiences following the conclusion of the 2016 Rio Olympic Games, including the factors that may have contributed to or challenged their well-being during this time. Eighteen athletes participated in semi-structured interviews and thematic analysis revealed that when Olympic performance appraisal met prior expectations, when athletes planned for a return to work or study, and when support from a variety of sources was readily available, this positively influenced athletes’ well-being during the POP. When these factors were not in place, more challenging post-Games experiences were present, and well-being was compromised. The findings contribute to the broader literature on elite athlete well-being and at an applied level, may be used to inform targeted programs that focus on supporting athletes after an Olympic campaign.